CRIMINAL POLICY IN LAW ENFORCEMENT RELATED TO MALPUBLIC ADMINISTRATION - Efendi, Jonaedi; Sholehuddin, M. (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2022)
The issue of penal politization has been cited by Dionysios Spinellis in his presentation concerning Top hat Crimes in Penal Law Summit XV of 1994. Application of penal law in the so called malpublic administration, refers to the three main issues in penal law. First, forms of malpublic administration acts which have been formulated as criminal act (criminalization process). Second, legal subjects that are liable for malpublic administration. Third, kinds and forms of sanctions applicable to the malpublic administration deeds (penalization process). Camus acknowledged justification of penalization to offender, but this penalization should not eliminate hir or her human power in obtaining new values  and new adaptation.